Peran Lembaga Adat dalam Penyelesaian Sengketa Tanah Ulayat (Studi Kasus di Daerah X) - Mubin, Muhamad; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research examines the role of customary institutions in resolving ulayat land disputes in Indonesia, focusing on dispute resolution mechanisms, factors affecting effectiveness, and challenges encountered. Using a descriptive-analytical normative-empirical legal approach, this research examines laws and regulations, court decisions, and related academic literature. The findings indicate that customary institutions such as the Nagari Customary Assembly in West Sumatra, the Riau Malay Customary Institution, and the Sulang Silima Marga Pakpak Customary Institution in North Sumatra play strategic roles as mediators, preservers of cultural values, and decision-making authorities respected by the community. The effectiveness of customary institutions is determined by internal factors such as human resource quality and community trust, as well as external factors such as clarity of territorial boundaries, legal recognition, and the younger generation's understanding of customary law. Challenges faced include minimal recognition from formal law, lack of documentation and written evidence, suboptimal inter-institutional coordination, and low interest among the younger generation in customary values. Synergy between customary institutions and formal law is essential to create legal certainty without disregarding social values. This research recommends strengthening customary institutional capacity, harmonizing customary and state regulations, documenting customary practices, and improving coordination with local land agencies.